Asia‐Inclusive Clinical Research and Development Enabled by Translational Science and Quantitative Clinical Pharmacology: Toward a Culture That Challenges the Status Quo - Venkatakrishnan, Karthik; Gupta, Neeraj; Smith, Patrick F.; Lin, Tiffany; Lineberry, Neil; Ishida, Tatiana; Wang, Lin; Rogge, Mark (Clinical pharmacology and therapeutics, 2023)
Access lag to innovative therapies in Asian populations continues to present a challenge to global health. Recent progressive changes in the global regulatory landscape, including newer guidelines, are enabling simultaneous global drug development and near‐simultaneous global drug registration. The International Conference on Harmonization (ICH) E17 guideline outlines general principles for the design and analysis of multiregional clinical trials (MRCTs). We posit that translational research and quantitative clinical pharmacology tools are core enablers for Asia‐inclusive global drug development aligned with ICH E17 principles. Assessment of ethnic sensitivity should be initiated early in the development lifecycle to inform the need for, and extent of, Asian phase I ethno‐bridging data. Relevant ethno‐bridging data may be generated as standalone Asian phase I trials, as part of Western First‐In‐Human trials, or under accelerated development settings as a lead‐in phase in an MRCT. Quantitative understanding of human clearance mechanisms and pharmacogenetic factors is vital to forecasting ethnic sensitivity in drug exposure using physiologically‐based pharmacokinetic models. Stratification factors to control heterogeneity in MRCTs can be identified by reverse translational research incorporating pharmacometric disease models and model‐based meta‐analyses. Because epidemiological variations can extend to the molecular level, quantitative systems pharmacology models may be useful in forecasting how molecular variation in therapeutic targets or pathway proteins across populations might impact treatment outcomes. Through prospective evaluation of conservation in drug‐ and disease‐related intrinsic and extrinsic factors, a pooled East Asian region can be implemented in Asia‐inclusive MRCTs to maximize efficiency in substantiating evidence of benefit‐risk for the region at‐large with a Totality of Evidence approach.